THE INFLUENCE OF ORGANIZATIONAL CULTURE ON POLICE PERFORMANCE OF NIAS POLICE RESCRIMING UNIT - Vice Kurniaman Zil Telaumbanua; Envilwan Berkat Harefa; Fatolosa Hulu (SEAN Institute, 2022)
This study aims to analyze the influence of organizational culture on police performance. Qualified police personnel is certainly related to the performance of police personnel or members. One factor that influences the performance of members in the police institution is organizational culture. The research method used is quantitative, with a survey to determine the influence between organizational culture variables and police performance variables. The population in this study is the Police Personnel of the Nias Police Criminal Investigation Unit. A regression test using SPSS 22 is used for hypothesis testing. The results showed a significant influence between organizational culture and police performance, evidenced by the positive organizational culture regression coefficient of 5.450. In the t-test, the value of t-count > t-table (5,450 > 0.681) means that there is partially a significant influence between organizational culture on police performance in the Nias Police Criminal Investigation Unit. Correlation analysis results obtained R of 0.662, which indicates that there is a strong relationship between organizational culture and police performance, namely rcount = 0.662 and rtable = 0.312, where obtained 0.662> 0.312.